1989
DOI: 10.1121/1.398608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two multichannel tactile aids for the hearing impaired

Abstract: Two multichannel tactile devices for the hearing impaired were compared in speech perception tasks of varying levels of complexity. Both devices implemented the "vocoder" principle in their stimulus processing: One device had a 16-element linear vibratory array worn on the forearm and displayed activity in 16 overlapping frequency channels; the other device delivered tactile stimulation to a linear array of 16 electrodes worn on the abdomen. Subjects were tested in several phoneme discrimination tasks, ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 0 publications
3
33
0
Order By: Relevance
“…The results of the two studies show similar performance: An average discriminability of 94% and dЈ of 3.5 were obtained in the present study when contrasting five voiced-unvoiced consonant pairs, indicating that the coding scheme used in Yuan, 2003 was a subset of the scheme used in the present study. The performance level obtained in the present study also appears to compare favorably with the results reported by earlier studies of tactual displays, where discrimination scores were generally less than 75% ͑Plant, 1989; Clements et al, 1988;Galvin et al, 1999;Waldstein and Boothroyd, 1995;Weisenberger et al, 1989;Summers et al, 2005͒. In addition to incorporating the amplitude information from low-and high-frequency speech bands, as in Yuan, 2003, our coding scheme displays energy information from the mid-frequency speech band in the form of temporal envelopes as well as low-frequency motion cues from the three speech bands to the corresponding fingerpads. To the best of our knowledge, this is the first time that low-frequency motion cues have been used to encode speech spectral information.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The results of the two studies show similar performance: An average discriminability of 94% and dЈ of 3.5 were obtained in the present study when contrasting five voiced-unvoiced consonant pairs, indicating that the coding scheme used in Yuan, 2003 was a subset of the scheme used in the present study. The performance level obtained in the present study also appears to compare favorably with the results reported by earlier studies of tactual displays, where discrimination scores were generally less than 75% ͑Plant, 1989; Clements et al, 1988;Galvin et al, 1999;Waldstein and Boothroyd, 1995;Weisenberger et al, 1989;Summers et al, 2005͒. In addition to incorporating the amplitude information from low-and high-frequency speech bands, as in Yuan, 2003, our coding scheme displays energy information from the mid-frequency speech band in the form of temporal envelopes as well as low-frequency motion cues from the three speech bands to the corresponding fingerpads. To the best of our knowledge, this is the first time that low-frequency motion cues have been used to encode speech spectral information.…”
Section: Discussionsupporting
confidence: 79%
“…The pairwise discrimination performance of the manner of articulation and voicing features was satisfactory ͑71% for voicing and 80% for manner͒ but discriminability of place of articulation distinction was poorer, i.e., 66%. Even with the multi-channel spectral display of the Queen's vocoder studied by Weisenberger et al ͑1989͒, place of articulation was not discriminated as well as other features ͑65% for place compared to 75% for manner and 70% for voicing͒. In other studies, discriminability of place of articulation was at chance level ͑Waldstein and Boothroyd, 1995;Plant, 1989;Summers et al, 2005;Weisenberger and Percy, 1995;Galvin et al, 1999͒. Therefore, it appears that the present coding scheme was able to transmit the place of articulation feature more successfully than has been demonstrated previously.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Reed [17], in this session, discusses Tadoma, a method used by a small number of deaf-blind people to perceive speech through their hands. Developments in artificial sensory substitution have afforded further evidence that speech can be perceived via touch [18,19,20,21,22].…”
Section: Historical Backgroundmentioning
confidence: 99%